Faktor-Faktor Yang Mempengaruhi Non-Performing Loan Pada Bank BUMN di Indonesia Tahun 2010-2019 - Firmansyah Firmansyah; Muh. Sari Sam (Universitas Mataram, 2022)
The high level of NPL will also put pressure on banks to maintain their capital. The risk is that when banks strengthen their capital, this will automatically reduce the ability of banks to expand credit to the real sector which will have an impact on the country's economy. The factors that caused the NPL problem were the lack of good faith from the debtors to immediately pay off their debts at a predetermined time. Then the banking policy to maintain high credit interest rates amidst unstable economic conditions also contributed to the increase in NPL. Banking carelessness in channeling was also one of the factors driving the increase in NPLs. This study aims to determine the effect of Loan to Asset Ratio, Third Party Funds, Earning Asset Quality and Credit Interest Rates on Non-Performing Loans at BUMN Banks in Indonesia 2010-2019. This type of research is explanatory, the type of data used is quantitative by using secondary data in the form of financial reports from the four state-owned banks. This study used multiple linear regression data analysis and partial test and simultaneous test using SPSS 2.2. The results of the analysis show that simultaneously the Loan to Asset Ratio, Third Party Funds (DPK), Earning Asset Quality and Credit Interest Rates have a significant effect on Non Performing Loans (NPL). Partially Loan to Asset Ratio, Third Party Funds have a negative and significant effect on Non- Performing Loans, Earning Asset Quality has a positive and significant effect on Non-Performing Loans. Meanwhile, the Lending Rate has no effect on Non-Performing Loans.